The Dichotomy in Evaluating Hadiths on the Dajjal's Tribulation: Analysis of Tirmidzi's Hasan Sahih Hadith vs Albani's Critique - Husna, Himmayatul; Najib Junaidi (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2025)
This article discusses the dichotomy in the evaluation of hadiths regarding the tribulation (fitnah) of the Dajjal, focusing on the differing assessments between Tirmidzi’s classification of a hadith as hasan sahih and the critique presented by Shaykh Muhammad Nasiruddin Albani. This approach aims to understand the differences in methodology and criteria used by these two scholars in hadith evaluation, as well as the implications for the authenticity and validity of the hadiths related to the Dajjal's tribulation. Through a comparative study, the article highlights the importance of contextual hadith evaluation in determining its status within the science of hadith and its implications for Islamic eschatology. The study concludes that Albani deemed the hadith dhaif because its content contradicts stronger narrations. In contrast, Tirmidzi’s classification of the hadith as hasan sahih suggests that such contradictions can be reconciled. This preference for reconciliation rather than prioritizing one narration over another aligns with the view of the majority of scholars who have commented on the hadith. The findings indicate that this difference in evaluation reflects diverse methodologies and emphases, underscoring the need for a critical and holistic approach in assessing hadiths related to the Dajjal’s tribulation